High-Power Large-Energy Rectangular Mode-Locked Er-Doped Fiber Laser Based on High-Damage-Threshold MoS2 Saturable Absorber - Pengfei Ma; Wei Lin; Huanian Zhang; Shanhui Xu; Zhongmin Yang (IEEE Photonics Journal)
In our work, based on chemical vapor deposition method and a newly designed glass–material–glass sandwich structure, MoS2 saturable absorber (SA) with a damage threshold of higher than 0.26 J/cm2 was fabricated and employed for demonstrating high-power, large-energy rectangular mode-locked Er-doped laser operation. Stable mode-locked operation with maximum output power of 122.77 mW and largest pulse energy of 130.49 nJ were successively achieved along with power scaling process. In comparison with previous works, our results show remarkable breakthroughs both in the aspects of average output power and pulse energy. Our experimental design and results will open a new avenue for generating high-power, large-energy mode-locked fiber lasers based on two-dimensional materials as SAs.